2021
DOI: 10.1177/03000605211010059
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of peripheral blood inflammatory cell subsets in patients with acute coronary syndrome undergoing percutaneous coronary intervention

Abstract: Objective This study aimed to investigate the predictive value of inflammatory cells in peripheral blood on the prognosis of patients with acute coronary syndrome (ACS) undergoing percutaneous coronary intervention (PCI). Methods Patients (n=1558) were consecutively enrolled and the median follow-up was 1142 days. Patients were divided into the major adverse cardiac events (MACE) 1 group (n=63) (all-cause mortality [n=58] and rehospitalization for severe heart failure [n=5], no MACE1 group (n=1495), MACE2 grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 39 publications
0
15
0
1
Order By: Relevance
“…The counts of lymphocyte, platelet, neutrophil, and monocyte were measured in the Central Laboratory of Beijing Anzhen Hospital. In this study, the lymphocyte-based inflammatory indices included: PLR (platelet/ lymphocyte), NLR (neutrophil/ lymphocyte), MLR (monocyte/ lymphocyte), SII (platelet * neutrophil/ lymphocyte), and SIRI (neutrophil * monocyte/ lymphocyte) ( 15 , 18 ). The GRACE risk score was analyzed as a numerical value and calculated according to the GRACE risk model by using a computer program ( http://www.outcomes-umassmed.org/grace ).…”
Section: Methodsmentioning
confidence: 99%
“…The counts of lymphocyte, platelet, neutrophil, and monocyte were measured in the Central Laboratory of Beijing Anzhen Hospital. In this study, the lymphocyte-based inflammatory indices included: PLR (platelet/ lymphocyte), NLR (neutrophil/ lymphocyte), MLR (monocyte/ lymphocyte), SII (platelet * neutrophil/ lymphocyte), and SIRI (neutrophil * monocyte/ lymphocyte) ( 15 , 18 ). The GRACE risk score was analyzed as a numerical value and calculated according to the GRACE risk model by using a computer program ( http://www.outcomes-umassmed.org/grace ).…”
Section: Methodsmentioning
confidence: 99%
“…Previously, we described the SII, dNLR, NLR, PLR, and MLR as suitable laboratory markers for identifying high-risk ACS patients after PCI. 10 , 11 In recent years, new systemic inflammation markers, such as AISI, SIRI, and NLPR, have attracted the attention of many researchers because they include multiple components of CBC and are also easy to obtain. Monocytes and neutrophils are part of the innate immune system and produce pro-inflammatory mediators.…”
Section: Discussionmentioning
confidence: 99%
“… 9 Recently published studies have demonstrated that many combined ratios of CBC parameters, such as systemic immune-inflammatory index (SII), derived neutrophil-to-lymphocyte ratio (dNLR), neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), and monocyte-to-lymphocyte ratio (MLR), could be useful prognostic markers in ACS patients undergoing PCI. 10 , 11 Furthermore, as more complicated and newly mentioned inflammatory markers, the aggregate index of systemic inflammation (AISI), systemic inflammation response index (SIRI), and neutrophil-to-lymphocyte*platelet ratio (NLRP) have only been proposed simultaneously as biomarkers for predicting mortality in COVID-19 patients. 9 , 12 , 13 However, no studies have investigated the prognostic capacity of these 3 novel indices for ACS prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…Điểm cắt tối ưu của NLR, MPVLR lần lượt là 3,02 và 2,91 (độ nhạy và độ đặc hiệu như bảng 3), AUC>0,7 và có ý nghĩa thống kê (p<0,05). Các nghiên cứu khác của các tác giả Dong-Hyun Choi và cộng sự (2018) [7], Ahmed Mohammed Shumilah (2021) [8], Xiuxin Gao (2021) [9], Xue-Ting Li (2020) [10], Willim H. (2021) [11] cũng đã ghi nhận các tỉ số này có giá trị tiên lượng độc lập cho biến cố tim mạch ở HCVC.…”
Section: Giá Trị Tiên Lượng Biến Cố Tim Mạch Chính Của Tỉ Số Tế Bào Viêmunclassified